2012
DOI: 10.4103/0019-509x.98943
|View full text |Cite
|
Sign up to set email alerts
|

The frequency and spectrum of K-ras mutations among Iraqi patients with sporadic colorectal carcinoma

Abstract: The K-ras mutations are frequently encountered among Iraqi sporadic CRC patients, with relative higher frequencies of G>T transversions and Gly>Val codon 12 substitutions than encountered in their counterparts in developed countries. The latter is most likely to be related to differences in local carcinogens exposure, an aspect which requires further scrutiny.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 39 publications
0
17
1
1
Order By: Relevance
“…The disease ranking in this study unlike the results cited by the same country and even the neighbor countries, the reason is attributed to the variation in the colorectal cancer epidemiology in different geographical regions 37 .…”
Section: Histopathologicalevaluation Of Colorectal Carcinomacontrasting
confidence: 85%
“…The disease ranking in this study unlike the results cited by the same country and even the neighbor countries, the reason is attributed to the variation in the colorectal cancer epidemiology in different geographical regions 37 .…”
Section: Histopathologicalevaluation Of Colorectal Carcinomacontrasting
confidence: 85%
“…One such report that demonstrated high preponderance of Gly to Val was from a subset of Iraqi patients. [42] The genetic alterations occurred significantly more frequently in tumors of the left side of the colon as compared to the right side of the colon, in contrast to other reports which show a right sided shift. [43,44] Similar pattern, as observed in our study for mutational preference in KRAS, was earlier observed in a multicentric study on molecular screening in 1093 colorectal adenomas [45] and also from a study reported on Turkish CRC patients [46] , thus indicating a difference in the biological behavior.…”
Section: Discussionmentioning
confidence: 72%
“…[22] In Oman, [23] 79 CRC patients were checked that 48.1% had mutation and no relation was noticed with wild-type or mutant KRAS with recurrence-free survival and overall survival. In Iraq, [24] fifty CRC patients (mean age: 55.4 years and 54% males) enrolled that 48% had KRAS mutation, and there were no significant associations of age, gender, tumor location or histology, grading, staging, or lymphovascular invasion with KRAS mutation status. In the present study, there was no significant difference between clinicopathological factors with KRAS mutation status, except for age that KRAS mutation frequency was higher in age ≥50 years.…”
Section: Discussionmentioning
confidence: 97%